High-strength anti-ultraviolet liquid crystal polymer fiber and preparation method thereof

The preparation method of liquid crystal polymer fibers with benzotriazole groups introduced through specific monomer ratios and chemical polymerization solves the problem of aging of high-strength synthetic fibers under ultraviolet light, and achieves high-strength and long-life liquid crystal polymer fibers , meets the tensile and ultraviolet resistance requirements of outdoor cables.

CN119194645APending Publication Date: 2024-12-27宁波聚嘉新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411383085.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing high-strength synthetic fibers have weak aging performance under ultraviolet light, resulting in faster damage to cables during outdoor use, increasing replacement and maintenance costs, and reducing service life.

Method used

Preparation methods of liquid crystal polymer fibers with specific monomer ratios include prepolymerization, solid phase polycondensation and heat treatment, introduction of benzotriazole groups, improving UV resistance through chemical polymerization, and spraying fiber filaments through spinning components Styling and winding to form high-strength, ultraviolet-resistant liquid crystal polymer fibers.

Benefits of technology

The high strength and long-lasting UV resistance properties of liquid crystal polymer fibers are achieved, and the tensile strength can reach more than 3.38GPa. The strength retention rate after 1000 hours of anti-aging test is still above 97.4%, meeting the strength and UV resistance of outdoor cables. Performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070371240000021
    Figure BDA0005070371240000021
  • Figure BDA0005070371240000031
    Figure BDA0005070371240000031
  • Figure BDA0005070371240000032
    Figure BDA0005070371240000032
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and relates to a preparation method of a high-strength anti-ultraviolet liquid crystal polymer fiber. The preparation method specifically comprises the following steps: mixing p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-alcohol and terephthalic acid with an acylation reagent and a catalyst according to a specific ratio to obtain a reaction mixture; carrying out prepolymerization reaction on the reaction mixture to obtain a prepolymer; carrying out solid-phase polycondensation reaction on the prepolymer in an inert gas atmosphere to obtain a liquid crystal polymer; heating and extruding the liquid crystal polymer, then supplying the liquid crystal polymer to a spinning assembly, spraying fibers through the spinning assembly, and carrying out heat preservation, air cooling, drafting and shaping, and yarn separation and rolling on the fibers to obtain nascent fibers; the nascent fiber is subjected to heat treatment to obtain the finished fiber, the tensile strength can reach 3.38 GPa or above, the strength retention rate still reaches 97.4% or above after a 1000-hour anti-aging test, and the high requirements of outdoor cables on the tensile element strength and the anti-ultraviolet performance can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a high-strength UV-resistant liquid crystal polymer fiber and a preparation method thereof. Background Art

[0002] In recent years, as communication technology products have developed towards miniaturization and lightweight, the cable industry has also accelerated the development of special small, soft and lightweight cables. Such cables often need to be stretched and bent multiple times during use. Therefore, the core component of the conductive core layer needs to be supported by tensile elements to resist the external forces caused by stretching and bending.

[0003] At present, the tensile elements used in cable cores include steel wire and synthetic fiber. Steel wire has the characteristics of high strength, low elongation and low price, and is widely used in many occasions. However, steel wire also has its own inevitable disadvantages, namely, large mass and poor softness. In order to make up for the shortage of steel wire, high-strength synthetic fiber has gradually come into people's view. The common characteristics of this kind of material are low density and high strength, which can reach the strength of steel wire, or even twice the strength of steel wire. Therefore, it is increasingly put into the actual production of cables. However, high-strength synthetic fiber also has a more obvious use defect, that is, its anti-aging performance is weak. Cables are used outdoors and cannot avoid ultraviolet light exposure. Ultraviolet light has strong penetrability and has the energy required to cause the breakage of various chemical bonds on the polymer chain. It is easy to penetrate the outer sheath layer to cause aging damage to the synthetic fiber inside the cable, resulting in damage to the cable or increased loss, which not only greatly increases the replacement and maintenance costs of the cable, but also greatly reduces the service life of the cable.

[0004] As the ozone layer continues to be destroyed, the UV index will become higher and higher, which will put higher requirements on the UV resistance of cable tensile components. Summary of the invention

[0005] The object of the present invention is to provide a high-strength, UV-resistant liquid crystal polymer fiber and a preparation method thereof in view of the above technical problems.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing high-strength UV-resistant liquid crystal polymer fiber, comprising the following preparation steps:

[0007] S1: Mixing monomers p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid with an acylating agent and a catalyst to obtain a reaction mixture; wherein, in terms of molar percentage, the molar percentages of the four monomers are as follows: p-hydroxybenzoic acid 60-85 mol%, 6-hydroxy-2-naphthoic acid 12-24 mol%, 7-amino-1H-benzotriazole-4-ol 1.5-8 mol%, terephthalic acid 1.5-8 mol%, and the structural formulas of the four monomers are as follows:

[0008] Parabens

[0009]

[0010] 6-Hydroxy-2-naphthoic acid

[0011]

[0012] 7-Amino-1H-benzotriazol-4-ol

[0013]

[0014] Terephthalic acid

[0015]

[0016] S2: subjecting the reaction mixture to a prepolymerization reaction to obtain a prepolymer;

[0017] S3: Under an inert gas atmosphere, subjecting the prepolymer to a solid phase polycondensation reaction to obtain a liquid crystal polymer;

[0018] S4: heating and extruding the liquid crystal polymer, and then supplying the liquid crystal polymer to a spinning assembly, spraying fiber filaments through the spinning assembly, and performing heat preservation, air cooling, drawing and shaping, and filament separation and winding on the fiber filaments to obtain nascent fibers;

[0019] S5: heat-treating the spun fibers to obtain finished fibers.

[0020] Preferably, in step S1, the molar ratio of 7-amino-1H-benzotriazole-4-ol to terephthalic acid is 1:1.

[0021] Preferably, the catalyst in step S1 is dibutyltin oxide, and the added amount is 70-150 ppm based on the total weight of the four monomers.

[0022] Preferably, the acylating agent in step S1 is at least one of acetic anhydride, propionic anhydride and maleic anhydride, and the added amount is 1.1-1.3 times the total molar number of the amino groups and hydroxyl groups of the four monomers.

[0023] Preferably, the step S2 comprises: keeping the reaction mixture at 110-140°C for 2-5h, then heating to 280-310°C, keeping for 1-3h, crushing, and drying at 110-130°C for 2-3h to obtain the prepolymer.

[0024] Preferably, the inert gas in step S3 is at least one of nitrogen, argon and carbon dioxide.

[0025] Preferably, the solid phase polycondensation temperature in step S3 is 260-300° C. and the time is 12-48 hours.

[0026] Preferably, the heat treatment temperature in step S5 is 270-320°C and the time is 12-24 hours.

[0027] The second object of the present invention is to provide a high-strength anti-ultraviolet liquid crystal polymer fiber, which is prepared by a preparation method of the high-strength anti-ultraviolet liquid crystal polymer fiber.

[0028] The beneficial technical effects of the present invention are:

[0029] The present invention obtains liquid crystal polymers that can be used for stable spinning by regulating the specific content of monomers, and introduces benzotriazole groups by chemical polymerization, which greatly improves the anti-ultraviolet performance of the polymer and avoids the migration or volatilization loss caused by the addition of the polymer as a small molecule alone. The fiber made of the liquid crystal polymer obtained by the monomer combination of the present invention not only has high strength, with a tensile strength of more than 3.38 GPa, but also has long-lasting anti-ultraviolet properties. After 1000 hours of anti-aging test, the strength retention rate is still more than 97.4%, which can meet the high requirements of outdoor cables for tensile component strength and anti-ultraviolet performance. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the specific embodiments of the present invention are described in detail below. Unless otherwise specified, materials, equipment and reagents are all commercially available.

[0031] A method for preparing high-strength UV-resistant liquid crystal polymer fiber, comprising the following preparation steps:

[0032] S1: Mixing monomers p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid with an acylating agent and a catalyst to obtain a reaction mixture; wherein, in terms of molar percentage, the molar percentages of the four monomers are as follows: p-hydroxybenzoic acid 60-85 mol%, 6-hydroxy-2-naphthoic acid 12-24 mol%, 7-amino-1H-benzotriazole-4-ol 1.5-8 mol%, terephthalic acid 1.5-8 mol%, and the structural formulas of the four monomers are as follows:

[0033] Parabens

[0034]

[0035] 6-Hydroxy-2-naphthoic acid

[0036]

[0037] 7-Amino-1H-benzotriazol-4-ol

[0038]

[0039] Terephthalic acid

[0040]

[0041] S2: subjecting the reaction mixture to a prepolymerization reaction to obtain a prepolymer;

[0042] S3: Under an inert gas atmosphere, subjecting the prepolymer to a solid phase polycondensation reaction to obtain a liquid crystal polymer;

[0043] S4: heating and extruding the liquid crystal polymer, and then supplying the liquid crystal polymer to a spinning assembly, spraying fiber filaments through the spinning assembly, and performing heat preservation, air cooling, drawing and shaping, and filament separation and winding on the fiber filaments to obtain nascent fibers;

[0044] S5: heat-treating the spun fibers to obtain finished fibers.

[0045] Optionally, in step S1, the molar ratio of 7-amino-1H-benzotriazole-4-ol to terephthalic acid is 1:1.

[0046] Optionally, in step S1, the catalyst is dibutyltin oxide, and the added amount is 70-150 ppm based on the total weight of the four monomers.

[0047] Optionally, in step S1, the acylating agent is at least one of acetic anhydride, propionic anhydride and maleic anhydride, and the added amount is 1.1-1.3 times the total molar number of the amino groups and hydroxyl groups of the four monomers.

[0048] Optionally, the reaction mixture in step S2 is subjected to a prepolymerization reaction to obtain a prepolymer, comprising: keeping the reaction mixture at 110-140°C for 2-5h, then heating it to 280-310°C and keeping it for 1-3h, then filling a Hastelloy kettle with 0.5-1.0MPa inert gas, discharging the reaction product through a discharge valve with a diameter of 2-4mm and 8-10 holes, crushing it, passing it through a 20-30 mesh sieve, and drying it at 110-130°C for 2-3h to obtain the prepolymer.

[0049] Optionally, the inert gas in step S3 is at least one of nitrogen, argon and carbon dioxide.

[0050] Optionally, in step S3, the solid phase polycondensation temperature is 260-300° C. and the time is 12-48 hours.

[0051] Optionally, in step S4, the liquid crystal polymer is heated to 280-320° C. and then extruded.

[0052] Optionally, the insulation temperature in step S4 is 270-300° C., and the speed of the drawing and shaping is 800-1000 m / min.

[0053] Optionally, the heat treatment temperature in step S5 is 270-320°C and the time is 12-24 hours.

[0054] The second object of the present invention is to provide a high-strength anti-ultraviolet liquid crystal polymer fiber, which is prepared by a preparation method of the high-strength anti-ultraviolet liquid crystal polymer fiber.

[0055] The invention obtains a liquid crystal polymer that can be used for stable spinning by regulating the specific content of monomers, and introduces a benzotriazole group by chemical polymerization, thereby greatly improving the anti-ultraviolet performance of the polymer, and avoiding the migration or volatilization loss caused by the single addition of 7-amino-1H-benzotriazole-4-ol as a small molecule; the liquid crystal polymer obtained by combining the monomers of the invention into fibers not only has high strength, with a tensile strength of more than 3.38 GPa, but also has a lasting anti-ultraviolet property. After a 1000-hour anti-aging test, the strength retention rate is still more than 97.4%, which can meet the high requirements of outdoor cables for tensile component strength and anti-ultraviolet performance.

[0056] In order to further illustrate the present invention, several specific examples are given below. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0057] Table 1 is a table of monomer ratios in Examples 1-5.

[0058] Table (1)

[0059]

[0060] Example 1

[0061] According to the 1# ratio, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid, acetic anhydride as an acylating agent accounting for 1.1 times the total molar amount of the amino groups and hydroxyl groups of the four monomers, and dibutyltin oxide as a catalyst accounting for 70 ppm of the total weight of the four monomers are mixed to obtain a reaction mixture; the reaction mixture is kept at 110° C. for 5 hours, then the temperature is increased to 280° C. and kept for 1 hour, and then 0.5 MPa of inert gas is filled into a Hastelloy kettle, and the reaction product material is discharged through a discharge valve with a diameter of 2 mm and 8 holes, crushed, passed through a 30-mesh sieve, and dried at 110° C. for 3 hours to obtain the prepolymer; under a nitrogen gas atmosphere, the above prepolymer is subjected to solid phase polycondensation at 260° C. in a rotary kiln for 48 hours to obtain a liquid crystal polymer.

[0062] The liquid crystal polymer is heated to 280°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept warm at 270°C, air-cooled, and drawn, shaped, and wound at a speed of 800 m / min to obtain spun fibers; the spun fibers are heat-treated at 270°C for 24 hours to obtain high-strength UV-resistant liquid crystal polymer fibers.

[0063] Example 2

[0064] According to the 2# ratio, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid, acylating agent propionic anhydride accounting for 1.15 times the total molar amount of amino groups and hydroxyl groups of the four monomers, and catalyst dibutyltin oxide accounting for 90 ppm of the total weight of the four monomers are mixed to obtain a reaction mixture; the reaction mixture is kept at 120° C. for 3 hours, then the temperature is increased to 290° C. and kept for 2 hours, and then 0.6 MPa of inert gas is filled into the Hastelloy kettle, and the reaction product material is discharged through a discharge valve with a diameter of 2 mm and 8 holes, crushed, passed through a 30-mesh sieve, and dried at 120° C. for 2 hours to obtain the prepolymer; under a nitrogen gas atmosphere, the above prepolymer is subjected to solid phase polycondensation at 270° C. in a rotary kiln for 36 hours to obtain a liquid crystal polymer.

[0065] The liquid crystal polymer is heated to 290°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept warm at 280°C, air-cooled, and drawn, shaped, and wound at a speed of 850m / min to obtain spun fibers; the spun fibers are heat-treated at 280°C for 20h to obtain high-strength UV-resistant liquid crystal polymer fibers.

[0066] Example 3

[0067] According to the 3# ratio, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid, acetic anhydride as an acylating agent accounting for 1.2 times the total molar amount of the amino groups and hydroxyl groups of the four monomers, and dibutyltin oxide as a catalyst accounting for 100 ppm of the total weight of the four monomers are mixed to obtain a reaction mixture; the reaction mixture is kept at 130° C. for 3 hours, then the temperature is increased to 300° C. and kept for 2 hours, and then 0.8 MPa of inert gas is filled into a Hastelloy kettle, and the reaction product material is discharged through a discharge valve with a diameter of 4 mm and 8 holes, crushed, passed through a 20-mesh sieve, and dried at 120° C. for 3 hours to obtain the prepolymer; under a nitrogen gas atmosphere, the above prepolymer is subjected to solid phase polycondensation at 280° C. in a rotary kiln for 30 hours to obtain a liquid crystal polymer.

[0068] The liquid crystal polymer is heated to 300°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept warm at 290°C, air-cooled, and drawn, shaped, and wound at a speed of 900 m / min to obtain spun fibers; the spun fibers are heat-treated at 290°C for 18 hours to obtain high-strength UV-resistant liquid crystal polymer fibers.

[0069] Example 4

[0070] According to the 4# ratio, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid, acylating agent propionic anhydride accounting for 1.25 times the total molar amount of amino groups and hydroxyl groups of the four monomers, and catalyst dibutyltin oxide accounting for 130ppm of the total weight of the four monomers are mixed to obtain a reaction mixture; the reaction mixture is kept at 130°C for 4 hours, then the temperature is increased to 300°C and kept for 2 hours, and then 0.9MPa of inert gas is filled into the Hastelloy kettle, and the reaction product material is discharged through a discharge valve with a diameter of 2mm and 10 holes, crushed, passed through a 30-mesh sieve, and dried at 120°C for 2 hours to obtain the prepolymer; under an argon gas atmosphere, the above prepolymer is subjected to solid phase polycondensation at 290°C in a rotary kiln for 24 hours to obtain a liquid crystal polymer.

[0071] The liquid crystal polymer is heated to 310°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept warm at 290°C, air-cooled, and drawn, shaped, and wound at a speed of 900 m / min to obtain spun fibers; the spun fibers are heat-treated at 310°C for 15 hours to obtain high-strength UV-resistant liquid crystal polymer fibers.

[0072] Example 5

[0073] According to the 5# ratio, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid, acylating agent maleic anhydride accounting for 1.3 times the total molar amount of amino groups and hydroxyl groups of the four monomers, and catalyst dibutyltin oxide accounting for 150ppm of the total weight of the four monomers are mixed to obtain a reaction mixture; the reaction mixture is kept at 140°C for 2 hours, then the temperature is increased to 310°C and kept for 1 hour, and then 1.0MPa of inert gas is filled into the Hastelloy kettle, and the reaction product material is discharged through a discharge valve with a diameter of 2mm and 8 holes, crushed, passed through a 20-mesh sieve, and dried at 130°C for 2 hours to obtain the prepolymer; in a carbon dioxide gas atmosphere, the above prepolymer is subjected to solid phase polycondensation at 300°C in a rotary kiln for 12 hours to obtain a liquid crystal polymer.

[0074] The liquid crystal polymer is heated to 320°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept warm at 300°C, air-cooled, and drawn, shaped, and wound at a speed of 1000m / min to obtain spun fibers; the spun fibers are heat-treated at 320°C for 12h to obtain high-strength UV-resistant liquid crystal polymer fibers.

[0075] Comparative Example 1

[0076] The difference from Example 3 is that p-hydroxybenzoic acid is replaced by an equimolar amount of 6-hydroxy-2-naphthoic acid; the rest is the same as Example 3.

[0077] Comparative Example 2

[0078] The difference from Example 3 is that 6-hydroxy-2-naphthoic acid is replaced by an equimolar amount of p-hydroxybenzoic acid; the rest is the same as Example 3.

[0079] Comparative Example 3

[0080] The difference from Example 3 is that 7-amino-1H-benzotriazole-4-ol is replaced by an equimolar amount of p-aminophenol; the rest is the same as Example 3.

[0081] Comparative Example 4

[0082] The difference from Example 3 is that the monomer 7-amino-1H-benzotriazole-4-ol does not directly participate in the prepolymerization reaction. After the solid phase polycondensation is completed, the polymer after the solid phase polycondensation and an equal molar amount of 7-amino-1H-benzotriazole-4-ol in Example 3 are mixed, plasticized, and extruded in a screw extruder to obtain a liquid crystal polymer; the rest is the same as Example 3.

[0083] Comparative Example 5

[0084] The difference from Example 3 is that terephthalic acid is replaced by an equal molar amount of isophthalic acid; the rest is the same as Example 3.

[0085] The relevant performance test standards of the liquid crystal polymer fiber of the present invention are as follows:

[0086] (1) Tensile strength: The mechanical properties of liquid crystal polymer fibers were tested according to GB / T 19975-2005 test method for tensile properties of high-strength filaments;

[0087] (2) Anti-aging performance: The anti-aging performance of liquid crystal polymer fibers was tested according to the plastic laboratory light source exposure test method GB / T 16422.2-2014.

[0088] The results of Examples 1-5 and Comparative Examples 1-5 measured using the above performance testing method are shown in Table (2).

[0089] Table (2): Performance test results of Examples 1-5 and Comparative Examples 1-5

[0090]

[0091] The above-mentioned implementation mode is only a preferred technical solution of the present invention. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and working principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing high-strength UV-resistant liquid crystal polymer fiber, characterized in that: The preparation method comprises the following steps: S1: Mixing monomers p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 7-amino-1H-benzotriazole-4-ol, terephthalic acid with an acylating agent and a catalyst to obtain a reaction mixture; wherein, in terms of molar percentage, the molar percentages of the four monomers are as follows: p-hydroxybenzoic acid 60-85 mol%, 6-hydroxy-2-naphthoic acid 12-24 mol%, 7-amino-1H-benzotriazole-4-ol 1.5-8 mol%, terephthalic acid 1.5-8 mol%, and the structural formulas of the four monomers are as follows: Parabens 6-Hydroxy-2-naphthoic acid 7-Amino-1H-benzotriazol-4-ol Terephthalic acid S2: subjecting the reaction mixture to a prepolymerization reaction to obtain a prepolymer; S3: Under an inert gas atmosphere, subjecting the prepolymer to a solid phase polycondensation reaction to obtain a liquid crystal polymer; S4: heating and extruding the liquid crystal polymer, and then supplying the liquid crystal polymer to a spinning assembly, spraying fiber filaments through the spinning assembly, and performing heat preservation, air cooling, drawing and shaping, and filament separation and winding on the fiber filaments to obtain nascent fibers; S5: heat-treating the spun fibers to obtain finished fibers.

2. The method for preparing high-strength UV-resistant liquid crystal polymer fiber according to claim 1, characterized in that: In the step S1, the molar ratio of 7-amino-1H-benzotriazole-4-ol to terephthalic acid is 1:

1.

3. The method for preparing high-strength UV-resistant liquid crystal polymer fiber according to claim 1, characterized in that: The catalyst in step S1 is dibutyltin oxide, and the added amount is 70-150 ppm of the total weight of the four monomers.

4. The method for preparing high-strength UV-resistant liquid crystal polymer fiber according to claim 1, characterized in that: In step S1, the acylating agent is at least one of acetic anhydride, propionic anhydride and maleic anhydride, and the added amount is 1.1-1.3 times the total molar number of the amino groups and hydroxyl groups of the four monomers.

5. The method for preparing high-strength UV-resistant liquid crystal polymer fiber according to claim 1, characterized in that: The step S2 comprises: keeping the reaction mixture at 110-140° C. for 2-5 hours, then heating to 280-310° C., keeping the temperature for 1-3 hours, crushing, and drying at 110-130° C. for 2-3 hours to obtain the prepolymer.

6. The method for preparing high-strength UV-resistant liquid crystal polymer fiber according to claim 1, characterized in that: In step S3, the inert gas is at least one of nitrogen, argon and carbon dioxide.

7. The method for preparing high-strength UV-resistant liquid crystal polymer fiber according to claim 1, characterized in that: The solid phase polycondensation temperature in step S3 is 260-300° C. and the time is 12-48 hours.

8. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: The heat treatment temperature in step S5 is 270-320°C and the time is 12-24 hours.

9. A high-strength UV-resistant liquid crystal polymer fiber, characterized in that: The fiber is prepared by the method for preparing the high-strength UV-resistant liquid crystal polymer fiber according to any one of claims 1 to 8.